Analisis Dampak Konten Visual Palsu Berbasis Artificial Intelligence Terhadap Kepercayaan Masyarakat - Asri Adzariyatun Nisa; Muhammad Tendi Irawan; Rully Aldiansyah Kusnadi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
The development of Artificial Intelligence (AI) technology has brought significant changes to the creation and distribution of digital visual content. AI's ability to generate highly realistic images and videos has given rise to the phenomenon of fake visual content, such as deepfakes, which have the potential to mislead the public. This study aims to analyze the impact of AI-based fake visual content on public trust in digital information. The research method used was a qualitative approach through a literature review of national and international scientific journals relevant to the topics of AI, visual disinformation, and public trust. The study results indicate that the increasing spread of AI-based fake visual content contributes to a decline in public trust in digital media, fosters public skepticism, and triggers an information credibility crisis. Low levels of digital literacy and AI literacy are key factors exacerbating these impacts. Therefore, this study recommends efforts to improve digital literacy, strengthen regulations related to the use of AI, and implement ethical principles for technology to maintain and restore public trust.